Effectiveness of Current Practices for Disinfecting Medical Equipment in a Radiology Department. - Hubble, William L.; Austin Turner, James; Heuertz, Rita (Radiologic Technology)
Purpose To evaluate the effectiveness of routine, daily disinfection practices on the control of microorganisms on nuclear medicine equipment in a radiology department. Methods During phase 1, surface samples were collected from various sites in the nuclear medicine division of a radiology department at a single institution. These samples were transferred onto growth plates for evaluation and speciation by a clinical microbiologist. Collection sites that yielded potentially pathogenic bacteria or high numbers (> 100) of colonies of likely nonpathogenic bacteria were identified for resampling. During phase 2, secondary samples were taken at the resampling sites after disinfection. These secondary samples also were evaluated to determine the efficacy of the departmental disinfection practices on surface cleanliness. Results Phase 1 sampling identified 10 sites that harbored either potentially pathogenic bacteria or high numbers of likely nonpathogenic bacteria. Evaluation of post disinfection samples indicated elimination of potentially pathogenic bacteria and reduction of likely nonpathogenic colonies. Discussion The variety of surfaces and equipment found in radiology departments can present unique challenges for effective disinfection. Porous materials and intricate imaging and peripheral devices require special consideration when designing and maintaining department cleaning policies. Conclusion The disinfection practices in place at the institution were effective in reducing or eliminating bacteria; however, recolonization after cleaning was recognized as a possibility. Educating staff about the value of disinfecting contact surfaces between patients is necessary to achieve optimum sanitization in the radiology department.